Discussion about math, puzzles, games and fun. Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ π -¹ ² ³ °

You are not logged in.

- Topics: Active | Unanswered

Pages: **1**

**DodgyPerson****Member**- Registered: 2006-02-20
- Posts: 3

Ok i know it might be very simple for some people out here, but i am struggling with it:

I need to re-arrange the following formula in way so i can get Ns on its own!!!!

S = (Ns - N) / (Ns)

So as i said, i cant get Ns on its own!!!! WOuld be greatful if anyone could help!!!!

Offline

**George,Y****Member**- Registered: 2006-03-12
- Posts: 1,306

(Ns - N) / (Ns)=Ns/Ns-N/(Ns)=1-1/s

As long as S=1-1/s, no matter what N is ,the equation S = (Ns - N) / (Ns)

is valid. That means N is Undetermined by this equation! (N can be any number)

another example a+2N=a+N+N, can you solve N out?

**X'(y-Xβ)=0**

Offline

**ganesh****Moderator**- Registered: 2005-06-28
- Posts: 21,730

S = (Ns - N) / (Ns)

S(Ns)= Ns - N taking the denominator of the RHS to LHS

S(Ns) - Ns = -N (taking Ns to the LHS from RHS)

Ns - S(Ns) = N (rearranging the terms to make N on the RHS positive)

Ns (1 - S) = N (rearranging the LHS)

Therefore,

Ns = N / (1-S).

It is no good to try to stop knowledge from going forward. Ignorance is never better than knowledge - Enrico Fermi.

Nothing is better than reading and gaining more and more knowledge - Stephen William Hawking.

Offline

Pages: **1**